Extradigital Glomus Tumor of Thigh - Kemal Beksaç; Lutfi Dogan; Nazan Bozdogan; Gulay Dilek; Gokhan Giray Akgul; Cihangir Ozaslan (Case Reports in Surgery)
Glomus tumors are benign neoplasms that arise from neuromyoarterial glomus bodies. They represent around 1–5% of all soft-tissue tumors. High temperature, sensitivity, and pain and localized tenderness are the classical triad of symptoms. Most glomus tumors represent in the subungual area of digits. Extradigital glomus tumors are a very rare entity. There are rare cases of these tumors reported to be in shoulder, elbow, knee, wrist, even stomach, colon, and larynx. We are reporting a case of a glomus tumor on thigh and discuss the histological and immunohistochemical features.